The Implementation of Role Play to Improve EFL Speaking Skill of the Second Semester Students of Akademi Bahasa Asing Balikpapan - Muhammad Rochman (Universitas Cokroaminoto Palopo, 2014)
Speaking is an important skill learned by English student although English covers four skills namely speaking, listening, speaking and writing. Speaking is the main bridge for the students to master English. Unfortunately the fact has shown that the students were quite difficult to improve their speaking skill because they were accustomed to use their native language language in their daily life than using English. The above facts signify that the lecturer should apply the techniques that can motivate students to speak and engage students in encouraging activities. One of the techniques that encourage students to speak is role play. Role play is the choice implemented by the researcher in improving the speaking skill of the first year students at ABA Balikpapan since using role play, the students can express their idea, opinion, and feeling well in their performance without being worried to make mistake. Based on the result of the study, it can be concluded that the result of this research was satisfying. This research claims that it was successful in the effort in improving students’ English speaking skill through Role-Play. Role-Play activity could increase the students’ motivation in joining the teaching and learning activity. Their motivation is reflected in their efforts in preparing the Role-Play.